2014
DOI: 10.1002/pro.2473
|View full text |Cite
|
Sign up to set email alerts
|

Role of connecting loop I in catalysis and allosteric regulation of human glucokinase

Abstract: Glucokinase (GCK, hexokinase IV) is a monomeric enzyme with a single glucose binding site that displays steady-state kinetic cooperativity, a functional characteristic that affords allosteric regulation of GCK activity. Structural evidence suggests that connecting loop I, comprised of residues 47-71, facilitates cooperativity by dictating the rate and scope of motions between the large and small domains of GCK. Here we investigate the impact of varying the length and amino acid sequence of connecting loop I up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This region is located within a loop/β-strand motif that connects the large and small domains. 38 Notably, previous studies have identified several activating substitutions within this region, including S64P, a variant that displays NMR features characteristic of the α-type activation mechanism. 11,17 HDX-MS revealed increased deuterium uptake in this region, in agreement with a comparison of the unliganded and glucose bound crystal structures, demonstrating that this region is more solvent-exposed in the glucose-bound state (Figure 4, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…This region is located within a loop/β-strand motif that connects the large and small domains. 38 Notably, previous studies have identified several activating substitutions within this region, including S64P, a variant that displays NMR features characteristic of the α-type activation mechanism. 11,17 HDX-MS revealed increased deuterium uptake in this region, in agreement with a comparison of the unliganded and glucose bound crystal structures, demonstrating that this region is more solvent-exposed in the glucose-bound state (Figure 4, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a handful of activating mutations in GCK can cause hypoglycemia through excessive insulin secretion [11]. Many of these activating mutations map to connecting loop I (variably defined as aa 47-71 [19] or aa 62-72 [20]) in the GCK hinge, thereby confirming the functional importance of this region [11]. Connecting loop I exhibits dramatic structural flexibility as the enzyme reorganizes its two lobes in response to glucose [3, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these activating mutations map to connecting loop I (variably defined as aa 47-71 [19] or aa 62-72 [20]) in the GCK hinge, thereby confirming the functional importance of this region [11]. Connecting loop I exhibits dramatic structural flexibility as the enzyme reorganizes its two lobes in response to glucose [3, 19]. It is critical to the enzyme’s sigmoidal dependence on glucose [19], and it provides 4 contact residues (aa 62, 63, 65 and 66) for allosteric GCK activators [3, 21], thus making this region an allosteric site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, the knowledge about the specificity‐determining residues of the certain protein is far from complete. The residues non‐involved into the direct interaction may affect the molecular recognition by allosteric manner (Hubbard et al, ; Martinez et al, ). It hampers the evaluation of prediction accuracy, including the evaluation in comparison with other methods.…”
Section: Introductionmentioning
confidence: 99%